FOSTERING CONSERVANCY THROUGH BIOPROSPECTION: THE PHARMACEUTICAL VALUE OF THE BRAZILIAN ASCIDIAN FAUNA: Promovendo a conservação por meio da bioprospecção: o valor farmacêutico da fauna brasileira de ascídias - Del Bianco Sahm, Bianca; Alves Guimarães, Larissa; Veras Wilke, Diego; Bauermeister , Anelize; Veras Costa-Lotufo, Leticia; C. Jimenez, Paula (Arquivos de Ciências do Mar, 2022)
The inherent value of nature is immeasurable. That being said, through bioprospection – the systematic search for functional products or processes from living organisms –, the oceans and marine life have emerged as a relevant source of biodiscoveries that hold significant economic worth. Particularly considering the pharmaceutical industry, an increasing number of natural molecules of marine origin have been making their way into pipelines and receiving approval for clinical use. Still, in its earliest days, this had become an extractivist practice, putting marine environments at risk and nearly driving species to extinction through over-collecting. While it is now well understood that exploration of the oceans' living resources must withstand a sustainable agenda, thus, protecting the environment from unnatural genetic losses, it was the developments towards achieving more efficient bioprospective strategies and non-destructive but feasible means to assure product supply that pushed for the greatest advances in this field. Herein, we present our assessment of this story by telling it through the 20-year journey – and few detours –we took in the chemical and pharmacological study of the ascidian Eudistoma vannamei, a species endemic to the northeast coast of Brazil that retains novel natural products with remarkable modes of action. Indeed, ascidians figure among the most pharmacologically talented marine organisms, having yielded the active principles of three new anticancer drugs, one of which is being considered for repositioning towards the treatment of Covid-19. Finally, we argue that emphasizing the unceasing biotechnological potential of marine biological diversity, exemplified herein by Brazilian ascidians, but certainly true worldwide for this and many other groups, would work in favor of raising awareness and supporting strategies to foster conservation of the oceans. Keywords: blue biotechnology, marine biodiversity, ascidians, bioproducts, innovation.